Are Patagonia grasslands being overgrazed? A response to Marino et al. (2020). Issue 12 (20th September 2020) - Oliva, Gabriel; Paredes, Paula; Ferrante, Daniela; Cepeda, Carla; Rabinovich, Jorge
Abstract: Based upon primary productivity estimates, Oliva et al. (2019) concluded that, at the end of last century and after long periods of overgrazing, Patagonia's domestic stocks adjusted to regional‐scale herbivore carrying capacity. Populations of guanaco, a native camelid, increased thereafter, driving combined grazing pressures once again over carrying capacity in some areas. Marino et al. (2020) argued that grazing is not really at equilibrium because domestic stocks are concentrated in areas that remain overgrazed. They support the ideas that guanaco density is auto‐regulated by resource‐defence territoriality, and that guanacos are weak competitors with domestic stock, occupying only marginal areas. In their view, Oliva et al. (2019) put guanacos in the role of scapegoats, leaving domestic stocks unchecked. Equilibrium at regional scale does not preclude overgrazing and under‐grazing at local scales. By separating areas with and without domestic stocks, Marino et al. (2020) estimated overgrazing at 28% in Chubut Province and 73% in Santa Cruz Province. Our recalculations show 28% and 47% domestic overgrazing, respectively. However, when combined with guanaco densities, these increase to 48% for Chubut and 108% for Santa Cruz. We question the hypothesised lack of competitive value and efficient self‐regulating mechanisms that would prevent guanaco populations from overshooting carrying capacity. A dataset of 13 sheep farms showed mean density of 26 ± 3.8 guanacos/km 2 and high combined grazing pressures. This was also observed in a protected area of Chubut that reached 42 guanacos/km 2 and crashed during drought, with 60% mortality. Thereafter, guanacos increased to 70 guanacos/km 2, with recruitment rates that showed a complex response of density dependence but remained relatively elevated at densities above the estimated carrying capacity. Synthesis and applications . Marino et al. (2020) are right to question the apparent equilibrium of domestic stocks that are concentrated in areas that may be still overgrazed. But ground data show that guanaco populations have inefficient density population regulation and can reach densities well over carrying capacity, even in the presence of sheep. This does not mean that the main control should be on growing guanaco populations but it stresses our conclusion that joint management of the native‐domestic herbivore system is urgently needed. Joint management can be effected through local plans, as current guanaco management permits can only be issued in areas that are not overgrazed by sheep. Farm management plans may in this way transform an apparent competitor into a valuable resource, complementary to sheep raising. Abstract : Marino et al. (2020) are right to question the apparent equilibrium of domestic stocks that are concentrated in areas that may be still overgrazed. But ground data show that guanaco populations have inefficient density population regulation and can reach densities well over carrying capacity, even in the presence of sheep. This does not mean that the main control should be on growing guanaco populations but it stresses our conclusion that joint management of the native‐domestic herbivore system is urgently needed. Joint management can be effected through local plans, as current guanaco management permits can only be issued in areas that are not overgrazed by sheep. Farm management plans may in this way transform an apparent competitor into a valuable resource, complementary to sheep raising. Abstracta: Oliva et al. (2019) concluyeron que el ganado doméstico en la Patagonia, luego de décadas de sobrepastoreo, se estabilizó cerca de la capacidad de carga a fines del siglo pasado. Posteriormente las poblaciones de guanaco, un camélido nativo, crecieron y en algunas áreas la presión de herbivoría conjunta sobrepasó nuevamente la capacidad de carga. Marino et al. (2020) señalan que la ganadería se concentra solo en determinadas áreas que siguen sobrepastoreadas, que los guanacos se auto‐regulan a través de una defensa territorial y que son débiles competidores en sistemas mixtos con ovinos. Interpretan que Oliva et al. (2019) colocan al guanaco en el papel de chivo expiatorio y desvían la atención sobre el sobrepastoreo doméstico. Marino et al. (2020) pasaron por alto que un equilibrio a escala regional no excluye un posible sobre y sub‐pastoreo local. En este trabajo estimaron un 28% de sobrepastoreo doméstico en áreas ganaderas de Chubut y 73% en Santa Cruz. Nuestros estimaciones confirman 28% para Chubut y reducen el valor a 47% para Santa Cruz pero, con el agregado de guanacos, el sobrepastoreo sería de 48% y 108% respectivamente. Ponemos en duda la falta de competitividad y supuesta autorregulación eficiente de poblaciones de guanacos. Trece establecimientos mostraron además de ovinos 26 ± 3.8 SE guanacos/km 2 y presiones conjuntas de herbivoría muy elevadas. Un área protegida llegó a densidades de 42 guanacos/km 2, colapsó con 60% de mortalidad y creció nuevamente a 70 guanacos/km 2, con tasas de reclutamiento con una denso‐dependencia compleja pero que se mantuvieron relativamente elevadas incluso a densidades por sobre la capacidad de carga. Síntesis y aplicaciones . Concordamos con Marino et al. (2020) en que el ganado doméstico concentrado podría generar sobrepastoreo. Los datos de campo señalan sin embargo que los guanacos tienen mecanismos de autorregulación poco eficientes y pueden alcanzar densidades por encima de la capacidad de carga con o sin ovinos. Esto no quiere decir que el principal control deba ser sobre las poblaciones crecientes de guanacos, pero resalta la necesidad de manejo conjunto guanaco‐ovino, algo que es posible mediante planes de manejo prediales que deben ser autorizados solamente en areas que presentan sobrepastoreo doméstico y que podrían transformar al guanaco de un aparente competidor en un recurso valioso y complementario para la ganadería.